Invisible frontlines: Safeguarding the European energy infrastructure - Veronika Slakaityte; Izabela Surwillo (Danish Institute for International Studies (DIIS), 2024)
This report explores key challenges and priorities in safeguarding Europe's critical energy infrastructure against both physical and cyber threats amid rising geopolitical tensions. It follows recent sabotage incidents and the extensive development of new offshore energy infrastructure planned in maritime zones. Strengthening defenses against the multifaceted threats to Europe's energy system is crucial and the analysis is essential reading for grasping the urgent need for improved security measures and international collaboration to protect the continent's vital energy assets.
Keywords: 300; energy; infrastructure; the Baltic Sea Region; technology; energy politics; EU; Nord Stream